Photon Doppler velocimetry measurements of impact-induced surface waves in glass and their role in fracture initiation and damage evolution. (March 2022) - McDonald, Jason; Pena, Michael; Satapathy, Sikhanda; O'Toole, Brendan; Trabia, Mohamed; Jennings, Richard
Highlights: Rayleigh surface waves in brittle materials such as glass, due to high-velocity impact, can be observed using photon Doppler velocimetry. The observed surface waves show distinct structure due to initiation and evolution of fracture. State-of-the-art glass models appear to capture the initial fracture response but do not adequately capture the post fracture response. The motion of the impact surface, directly beneath the impact site, can also be observed in transparent materials. This technique can be extended to other brittle materials such as ceramics and diamond. Abstract: Ballistic experiments involving the impact of cylindrical Lexan® projectiles, with nominal velocities of 400 and 800 m/s, on borosilicate glass targets were conducted using a single-stage gas gun. The objective of the experiments was to develop a technique involving multiplexed photon Doppler velocimetry (PDV) to observe the distal surface motion due to the propagation of impact-induced elastic waves. Comparison of the recorded signals to finite-element simulations of the experiment allowed for the identification of the signature of fracture initiation and subsequent damage evolution in the material. By directing PDV probes through the rear surface of the target it was also found that the surface motion within the impact zone could be measured. In addition, it was discovered that two distinct velocity signals could be consistently measured beneath the impact site. One of these signals was identified as the particle velocity of the impact surface. The other signal is presently of unknown origin.